'You cannot do IVF in Africa as in Europe': the making of IVF in Mali and Uganda. (June 2016) - Hörbst, Viola
Abstract: In sub-Saharan Africa, many gynaecologists and embryologists agree that 'you cannot do IVF in Africa as in Europe'. Based on empirical data from anthropological fieldwork, this article contrasts the establishment of IVF provision in a private fertility clinic in (francophone, Muslim-dominated) Mali with one in (anglophone, Christian-dominated) Uganda. Outlining the history of setting up IVF procedures at each site, the author shows the distinct ways in which the respective clinics have found to juggle structural challenges. The question of how religious moral concepts are integrated in the way in which assisted reproductive technology is practised at the two sites is also considered, revealing the moral ambivalences of practitioners and patients, donors and surrogates. By contrasting the processes of setting up IVF therapeutics in a Malian and a Ugandan clinic, the author shows that sub-Saharan African countries, although sharing similar historical positioning in global power topographies, structural and political shortcomings, nevertheless exhibit a range of developments and societal answers in response to the challenges, both moral and structural, inherent in establishing assisted reproductive technology-based infertility treatment.